2019
DOI: 10.1177/0954406219891755
|View full text |Cite
|
Sign up to set email alerts
|

Multiobjective optimization of friction stir weldments of AA2014-T651 by teaching–learning-based optimization

Abstract: This study focuses on optimization of process parameters, which may result in improved mechanical properties of the friction stir weldments of AA2014-T651. Plain taper and threaded taper cylindrical tool pin profiles were used for the study. A set of experiments was conducted at different levels of tool rotational and weld speeds using two tool pin profiles. Mechanical properties such as tensile strength, yield strength, impact strength, percentage of elongation, and hardness were measured. Objective functions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…MATLAB R2019b software was used to develop the TLBO algorithm. TLBO requires the only size of the population and the total number of iterations to develop the algorithm [40]. The size of the population for the current study was fixed as 20 and the number of iteration as 50.…”
Section: Learner Levelmentioning
confidence: 99%
“…MATLAB R2019b software was used to develop the TLBO algorithm. TLBO requires the only size of the population and the total number of iterations to develop the algorithm [40]. The size of the population for the current study was fixed as 20 and the number of iteration as 50.…”
Section: Learner Levelmentioning
confidence: 99%
“…The TLBO algorithm is an algorithm which is inspired from teaching and learning capability of teacher and learner and knowledge is flows from teacher to learner to recognize all the ideas and implement best idea either from teacher or learner or from both to obtain optimum solution. 21,23 In this algorithm, a population is taken which is considered as group of learners and subjects given to the learners are taken as different design variables which is actually input processing parameters for the optimization problem. The best solution obtained from whole population is assumed as the teacher and this solution is also representing the optimum solution of objective function.…”
Section: Tlbo Algorithmmentioning
confidence: 99%
“…In their experiments, they found that TRS was the most influencing factor for TS while axial force does not significantly affect the TS. Venu et al 23 observed the mechanical properties of FSWed AA2014-T651 by plain and threaded tapered cylindrical pin tool using L9 orthogonal array design matrix. TRS and WS as input parameters and teaching-learning-based optimization (TLBO) algorithm as optimizing technique was selected to improve the joint properties.…”
Section: Introductionmentioning
confidence: 99%
“…1 A sizable number of studies have been reported highlighting the effect of the rotational and traverse speed on the evolution of FS weld microstructure and its resultant influence on properties. [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] During the initial FSW study, Hashimoto et al 19 found that the tool travel and rotational speed affect the quality of joint and formation of the defect. The plunge depth was found to be important in void formation.…”
Section: Introductionmentioning
confidence: 99%